1997
DOI: 10.1097/00001756-199703030-00038
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β-amyloid in the canine brain

Abstract: The distribution of amyloid-beta protein (A beta) in the canine brain was demonstrated by immunochemistry on serially sectioned tissues from 10 aged mixed breed dogs. Summation of quantitative data and relegation to anatomical sites for the 10 dogs showed A beta to be widely distributed in the cortex and hippocampus while completely absent in the brain stem and cerebellum. The highest density of A beta was in the dentate gyrus of the hippocampus. Cortical areas exhibiting the greatest A beta deposition were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…In aging human brains, A␤ deposition occurs early in the prefrontal cortex (Braak and Braak, 1997;Bussière et al, 2002). In vitro studies in beagle dogs report similar variability in A␤ accumulation with the earliest and most consistent deposition occurring in the prefrontal cortex at ϳ8 years of age (Yoshino et al, 1996;Hou et al, 1997;Satou et al, 1997;Head et al, 2000). In contrast, A␤ deposition in the entorhinal, parietal, and occipital brain regions does not appear consistently until after 12 years of age in the dog (Head et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…In aging human brains, A␤ deposition occurs early in the prefrontal cortex (Braak and Braak, 1997;Bussière et al, 2002). In vitro studies in beagle dogs report similar variability in A␤ accumulation with the earliest and most consistent deposition occurring in the prefrontal cortex at ϳ8 years of age (Yoshino et al, 1996;Hou et al, 1997;Satou et al, 1997;Head et al, 2000). In contrast, A␤ deposition in the entorhinal, parietal, and occipital brain regions does not appear consistently until after 12 years of age in the dog (Head et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have shown that aged dogs naturally develop diffuse plaques that contain beta-amyloid (Aβ) peptide similar to those observed in humans with mild cognitive impairment and AD (Wisniewski et al 1990;Cummings et al 1993;Hou et al 1997;Head et al 2000). Further, dogs and humans express the same 1-42 amino acid sequence Aβ peptide (Selkoe et al 1987;Johnstone et al 1991).…”
Section: Why Study Aging In Dogs?mentioning
confidence: 89%
“…As discussed previously, many of the commonly used models of AD utilize a variety of different promoters, resulting in variation in pathological topography. While canine Aβ pathology appears largely in the cortex and hippocampus (similar to humans), the brain stem, cerebellum, entorhinal cortex, amygdala, basal ganglia and olfactory bulbs are largely unaffected (Hou et al, 1997;Head et al, 2000). Aged rhesus macaques exhibit loss of cholinergic neurons, much like humans affected by AD, but the cortex of the macaque brain remains largely unaffected by AD-like pathology (Rapp and Amaral, 1992;Siddiqi and Peters, 1999).…”
Section: Alzheimer Disease Pathology and Basic Science Animal Researchmentioning
confidence: 99%
“…The extent of Aβ plaque pathology correlates with some measure of cognitive impairment, though, as in humans, Aβ plaque pathology has been identified in canines without any apparent cognitive symptoms (Sarasa and Pesini, 2009). Many treatment strategies in preclinical testing have been applied to canines (Head et al, 1998Cummings et al, 1996a;Colle et al, 2000;Hou et al, 1997). cells (Duyckaerts et al, 2008;Davis et al, 2012;Thyagarajan et al, 2003).…”
Section: Alzheimer Disease Pathology and Basic Science Animal Researchmentioning
confidence: 99%